Improving consumer awareness for reducing food waste using partial least squares structural equation modelling (PLS-SEM) approach - Ismat Jahan; Kazi Tamzid Kamal; Prattusha Bhattacharjee; Hasin Md. Muhtasim Taqi; Syed Mithun Ali (Cleaner and Responsible Consumption)
Food waste (FW) has become a major concern in the global era, which is affecting the societal environment and economy consistently. Rising population and urbanization have increased food production and consumption, especially in developing countries like Bangladesh. Due to limited recycling and disposal choices, FW is composted, landfilled, and fed to animals, creating a dirty and smelly environment. Such a situation needs elevated awareness and attention among consumers. Following the necessity, this study investigates the impact of consumer awareness on reducing FW in households and restaurants. Here, the partial least square structural equation modelling (PLS-SEM) was utilized to predict the factors that affect consumers behaviors relative to FW at household and restaurant levels. Two PLS-SEM were estimated, a normative and an explicative model. In the normative model, three multidimensional attitude components (affective, cognitive, and conative) were classified among the factors that influence food waste behaviour. The conative component was found to be the most influential. In the explicative model, improper meal storage emerged as the factor with the highest correlation with the generation of FW. The implication of this research encourages stakeholders to share research findings to work toward a sustainable and food-secure future.